Proactive Safety Culture Application (PROSCA) using geolocation / Muhammad Afzani Mahadzir, Nor Azylia Ahmad Azam and Muhammad Azhar Ab Razak - Mahadzir, Muhammad Afzani; Ahmad Azam, Nor Azylia; Ab Razak, uhammad Azhar (Faculty of Computer and Mathematical Sciences, 2023)
It is impossible to overstate the value of safety culture in creating a safe working environment and avoiding accidents at work. However, due to differing safety policies and human variables, its implementation frequently confronts obstacles in large-scale enterprises. The Proactive Safety Culture Application (PROSCA) is an application aims to enable enterprises in building a proactive safety culture via the use of cutting-edge technology interventions. Through the integration of novel technology, PROSCA strives to overcome these difficulties and redefine safety management. The PROSCA's design is supported by important safety culture factors like corporate commitment, employee involvement, and safety communication. PROSCA’s also are embedded with utilizing geolocation stands as a transformative approach to elevate workplace safety. By harnessing the potential of geolocation technology, PROSCA empowers employees with real-time safety insights and fosters a collective commitment to safety. This makes important advancements in the field of safety management and emphasizes the crucial part played by geolocation in establishing a proactive safety culture within organizations.